Self‐Assembled Wound Dressings Silence MMP‐9 and Improve Diabetic Wound Healing In Vivo. Issue 9 (23rd December 2015) - Castleberry, Steven A.; Almquist, Benjamin D.; Li, Wei; Reis, Tiago; Chow, John; Mayner, Sarah; Hammond, Paula T.
Abstract : The direct local delivery of short interfering RNA (siRNA) into target tissues presents a real solution to several complex medical conditions that today lack efficacious therapies. The development of an ultrathin polymer coating is described to sustain the delivery of siRNA for up to 2 weeks in vitro and in vivo. This technology successfully reduces the expression of MMP‐9 within the wounds of diabetic mice, significantly accelerating the wound healing process and improving the quality of tissue formed.